2018
DOI: 10.1073/pnas.1812122115
|View full text |Cite
|
Sign up to set email alerts
|

Self-cleavage of the glmS ribozyme core is controlled by a fragile folding element

Abstract: Riboswitches modulate gene expression in response to small-molecule ligands. Switching is generally thought to occur via the stabilization of a specific RNA structure conferred by binding the cognate ligand. However, it is unclear whether any such stabilization occurs for riboswitches whose ligands also play functional roles, such as the glmS ribozyme riboswitch, which undergoes self-cleavage using its regulatory ligand, glucosamine 6-phosphate, as a catalytic cofactor. To address this question, it is necessar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…4a, 5a). Consistent with our findings, P2.2 was previously proposed to play a key role in positioning the cleavage site and cofactor 17 , and more recently, the folding of this element was demonstrated directly to control catalysis 29 . We also found that the bottommost basepair of P2.2 (C2•G56) resulted in low activity (>850-fold below consensus) when changed to any alternative basepair (Fig.…”
Section: Double Mutant Cleavage Rates Reveal Mutational Interactionssupporting
confidence: 92%
“…4a, 5a). Consistent with our findings, P2.2 was previously proposed to play a key role in positioning the cleavage site and cofactor 17 , and more recently, the folding of this element was demonstrated directly to control catalysis 29 . We also found that the bottommost basepair of P2.2 (C2•G56) resulted in low activity (>850-fold below consensus) when changed to any alternative basepair (Fig.…”
Section: Double Mutant Cleavage Rates Reveal Mutational Interactionssupporting
confidence: 92%
“…Having established conditions and helper designs that yield strong protection and efficient site selectivity, we then proceeded to test the practical utility of the approach for acylation-based control of a tandem ribozyme. Although previous studies have described methods for control of a single catalytic RNA, the use of a tandem ribozyme (TR) here offered the possibility to selectively control one RNA function relative to another within the same strand. An 81nt tandem hammerhead ribozyme with dual catalytic cores (3TR and 5TR) was produced by in vitro transcription and was reacted under site-selective conditions at their catalytic cores by the RAIL method under the standard conditions (Figures a, S6a; see SI for details).…”
Section: Resultsmentioning
confidence: 99%
“…This mode of transcription control was also reported for the Bacillus cereus crcB fluoride aptamer 18,47 . In contrast, dynamic pseudoknot folding and unfolding mediate translation control by the Faecalibacterium prausnitzii class III preQ 1 riboswitch 48 and RNA degradation control by the GlmS riboswitch 49 .…”
Section: Discussionmentioning
confidence: 99%